A simplified approach to estimate the lifetime of structures subjected to earthquakes (2017)
This paper presents a stochastic model with which it is possible to know the Mean-Time-To-Failure of a structure and Mean-Time in which the performance levels of system are reached. The different parameters that influence the method, such as the structural period, the type of soil, the types of earthquakes that can be representative of the area of study and the seismic threat, are also taken into account. The fundamental basis of the model is the accumulation of seismic damage over time, in which the effect of damage by repetitive seismic events with medium-strong intensity is analyzed. Thanks to the method, it is given the opportunity to the different design codes to take into account the verification of the different limit states of the structure in order to guarantee the life of the system that is desired. The model is illustrated by an example and is compared to different scenarios in which...